Physicochemical Analysis and Antioxidant Activity of Onion Bulbs (Allium cepa L.) - Ladeska, Vera; Rindita; Amyra, Nur; Dwi Veranthy, Tamara (Tropical Biopharmaca Research Center, IPB University, 2020)
Allium cepa L. (onion bulb) is a cultivated onion extensively and types of onions that are often used for various cuisines in Indonesia. The onion bulb was efficient in reducing blood fat levels and diuretics. This study aims to complete the onion monograph with determine the physicochemical characteristics and antioxidant activity. Microscopic results obtained include: has fibrous roots and it’s white, and about 9.5 cm long. The stem is pseudo, and the water is whitish-green, cylindrical leaves are dark green, elongated like a pipe and hollow with a length of ± 20 cm, and the tip is tapered. Onion tubers are single layer bulbs, having a diameter of 6 mm, which is higher than onions. Microscopic results contained identification fragments, including hair covering and transporting beams with thickening stairs and spirals. From the results of research on ethanol extract, 70% Allium cepa L. shows a drying shrinkage of 9.69%, 5.16% total ash content, 0.07 % acid insoluble acid dust, 14.36% water-soluble extract, and soluble ethanol extracts 23.04%. Phytochemical screening contains flavonoids, saponins, phenols, dan triterpenoids. Total flavonoid content contained in ethanol extract of onion tubers was 1.48 ± 0.12 mg QE/g. Total phenolic concentrations obtained in onion tuber ethanol extract were 103.47 ± 3.09 mg GAE/g. The antioxidant activity of ethanol extract of onion tubers by the DPPH method received IC50 is 65.31 ppm.